2019
DOI: 10.1088/2053-1591/ab5f2c
|View full text |Cite
|
Sign up to set email alerts
|

Efficient CO2 adsorption using mesoporous carbons from biowastes

Abstract: The mesoporous carbon nanomaterials obtained from waste onion peels confirmed the formation of mesoporous carbon nanospheres (CNSs) with an average pore diameter of 2 nm. The as obtained CNSs were studied to demonstrate their ability to adsorb the greenhouse gas CO 2 at different temperatures, 30, 40 and 50°C. The results showed that the CNSs have high potential to adsorb CO 2 at these temperatures. Present work demonstrates the formation of sustainable, porous adsorbents by a simple waste to wealth based appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The results showed that when the mesoporous carbon support was modified by 80 wt% tetraethylenepentamine, the adsorbent had a high CO 2 capture amount of 5.3 mmol/g at 75 • C with excellent cycling stability. Apart from these, several other reports on the adsorption of different molecules have been seen in the literature [66][67][68][69][70]. As discussed above in this review, the mesoporous carbon materials with high specific areas are among the best materials to use as adsorbents.…”
Section: Adsorptionmentioning
confidence: 91%
“…The results showed that when the mesoporous carbon support was modified by 80 wt% tetraethylenepentamine, the adsorbent had a high CO 2 capture amount of 5.3 mmol/g at 75 • C with excellent cycling stability. Apart from these, several other reports on the adsorption of different molecules have been seen in the literature [66][67][68][69][70]. As discussed above in this review, the mesoporous carbon materials with high specific areas are among the best materials to use as adsorbents.…”
Section: Adsorptionmentioning
confidence: 91%
“…Thermal stability loss rate (%) carbon dioxide adsorbed increases first and then decreases [16,17]. Ganesan Sriram prepared the mesoporous carbon nanospheres (CNSs), which its CO 2 adsorption increased and then followed a reduction trend, at the three temperatures [18]. 273 K is the minimum temperature at which carbon dioxide adsorption can be measured.…”
Section: Amine Loading Of Pei On Sio 2 Aerogelsmentioning
confidence: 99%
“…Synthesized CNSs have been tested for various applications, such as electrode materials for energy storage devices and electrochemical sensors [37,42], in photomechanical actuators [43], and as materials for CO 2 adsorption [44], owing to the very high surface area and porosity. Such varied and increased use of nanoparticles leads to the exposure of humans to nanoparticles.…”
Section: Discussionmentioning
confidence: 99%